Distribution of childhood leukaemias and non-Hodgkin's lymphomas near nuclear installations in England and Wales. - Bithell, J; Dutton, S; Draper, G; Neary, N (1994)
OBJECTIVE: To examine the relation between the risk of childhood leukaemia and non-Hodgkin's lymphoma and proximity of residence to nuclear installations in England and Wales. DESIGN: Observed and expected numbers of cases were calculated and analysed by standard methods based on ratios of observed to expected counts and by a new statistical test, the linear risk score test, based on ranks and designed to be sensitive to excess incidence in close proximity to a putative source of risk. SETTING: Electoral wards within 25 km of 23 nuclear installations and six control sites that had been investigated for suitability for generating stations but never used. SUBJECTS: Children below age 15 in England and Wales, 1966-87. MAIN OUTCOME MEASURE: Registration of any leukaemia or non-Hodgkin's lymphoma. RESULTS: In none of the 25 km circles around the installations was the incidence ratio significantly greater than 1.0. The only significant results for the linear risk score test were for Sellafield (P = 0.00002) and Burghfield (P = 0.031). The circles for Aldermaston and Burghfield overlap; the incidence ratio was 1.10 in each. One of the control sites gave a significant linear risk score test result (P = 0.020). All the tests carried out were one sided with P values estimated by simulation. CONCLUSION: There is no evidence of a general increase of childhood leukaemia or non-Hodgkin's lymphoma around nuclear installations. Apart from Sellafield, the evidence for distance related risk is very weak.